Food Security During the COVID-19 Pandemic : Policy Comparison in Five Developing Countries in Asia - Silvia Dian Anggraeni; Ahmad Haris Hasanuddin Slamet; Ali Muhyidin (LP2M, 2022)
This study examines how the COVID-19 pandemic has impacted five developing Asian countries in terms of food security policies, particularly in Malaysia, Thailand, Saudi Arabia, Nepal, and Indonesia. These five countries have several differences, such as population, the quantity of main imported foods, food self-sufficiency policies, and natural resource conditions. This research uses a qualitative approach with literature study methods. The study shows that each country's initial policies in response to COVID-19, especially in terms of transportation mobility restriction, has impacted on food distribution. Domestic food stocks, subsidies, and government financial assistance are considered capable of maintaining food security temporarily. Nevertheless, domestic policies alone will not be sufficient to maintain and ensure long-term availability, affordability, and safety of food products. This study concludes that the optimization of local food production and imported food products is essential to maintain the balance of the supply chain of food in the country.